2011
DOI: 10.4061/2011/795239
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Cancer-Testis Antigens in Human Embryonic Stem Cells and Their Cell Derivatives Indicate Lineage Tracks

Abstract: Pluripotent stem cells can differentiate into various lineages but undergo genetic and epigenetic changes during long-term cultivation and, therefore, require regular monitoring. The expression patterns of cancer-testis antigens (CTAs) MAGE-A2, -A3, -A4, -A6, -A8, -B2, and GAGE were examined in undifferentiated human embryonic stem (hES) cells, their differentiated derivatives, teratocarcinoma (hEC) cells, and cancer cell lines of neuroectodermal and mesodermal origin. Undifferentiated hES cells and embryoid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…The Lu-iPSC exhibited similarities to other pluripotent cell lines reported in the literature (13) including surface antigen and stem cell gene expression profiles, in-vitro growth, and teratoma formation. Although previously reported to be activated in stem cells (36, 37), cancer-germline genes commonly up-regulated in lung cancers remained transcriptionally repressed in Lu-iPSC. These unexpected findings are consistent with a report by Loriot et al .…”
Section: Discussionmentioning
confidence: 79%
“…The Lu-iPSC exhibited similarities to other pluripotent cell lines reported in the literature (13) including surface antigen and stem cell gene expression profiles, in-vitro growth, and teratoma formation. Although previously reported to be activated in stem cells (36, 37), cancer-germline genes commonly up-regulated in lung cancers remained transcriptionally repressed in Lu-iPSC. These unexpected findings are consistent with a report by Loriot et al .…”
Section: Discussionmentioning
confidence: 79%
“…For instance, MAGE-A and N-RAGE (also known as MAGE-D1) were expressed by mesenchymal stem cells, but their expression levels decreased upon the differentiation of stem cells [37]. Similarly, the expression of MAGE-A3 and -A6 were detected in embryonic stem cells, but not in differentiated derivatives [38]. In addition, global gene expression analysis of CD133 + cells isolated from four different cord blood units identified trophinin as one of 32 genes that encode membrane proteins selectively expressed on CD133 + hematopoietic stem cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Vavilova 26, Moscow, 119334 Russia e mail: olgagordeeva@yandex.ru Expression of CTAs of MAGE families was mainly studied in various tumor cells in vitro or in the clinical samples of tumors of different origin (Sahin et al, 2000;Yuasa et al, 2001). However, there is no evi dence about their expression in the normal cells during prolonged culturing in vitro (Cronwright et al, 2005;Gjerstorff et al, 2008;Lifantseva et al, 2011). In our previous study, we assumed that expression of CTAs of MAGE families can be associated with development of early embryonic lines; whereas their aberrant expression can be associated with pathological pro cesses, particularly transformation and carcinogenesis .…”
Section: Expression Of Cancer Testis Antigens Of Mage a And Mage B Famentioning
confidence: 97%
“…Thus, it was found that Mage a and GAGE genes are specifically expressed during the development of human male and female germ cells (De Plaen et al, 1999;Aubry et al, 2001;Gaskell et al, 2004;Gjerstorff et al, 2006Gjerstorff et al, , 2007. Expression of the MAGE/Mage genes was revealed in human and mice pluripotent stem cells, as well as in the develop ing human neuroectodermal and mesodermal cells, and the human placenta cells (Andrieu et al, 2003;Deponti et al, 2007;Jungbluth et al, 2007;Kuwajima et al, 2006;Gjerstorff et al, 2008;Lifantseva et al, 2011).…”
Section: Introductionmentioning
confidence: 95%